"Forgetting the Stories Would Be Catastrophic": Writing the Oral and Protecting the Place in the Poems of Temsula Ao and Esther Syiem. Issue 1 (2nd January 2020) - Chakraborty, Sayantan
Abstract : Temsula Ao and Esther Syiem, two Indigenous poets from Ao-Naga and Khasi community of India's Northeast, want to tell traditional stories as community Elders to orally pass on the tradition to the next generation, but the present literate generation refuses to listen to these stories. Since the present literate generation insists on the written, these poets write down the oral in the form of poems. They actively engage in retelling the stories in written form to preserve the traditional meaning of place. These poets believe that the existence of the place is vital for the existence of their traditional culture; however, development projects compel them to dislocate and displace from their traditional place. Retelling also supports the land claim against development and mobilizes the community members to take responsibility in protecting and preserving the place. The central study of this article is understanding the complex function of Ao's and Syiem's retelling the oral stories in written poetic form in relation to place from a geographical approach.